Reforming Military Retirement Analysis in Support of the Military Compensation and Retirement Modernization Commission - Asch, Beth J. (RAND Corporation, 2015)
This report documents RAND analytical support to the Military Compensation and Retirement Modernization Commission (MCRMC). Using the Dynamic Retention Model, the report evaluates MCRMC's proposed military compensation and retirement plan reforms, by service, for officers and enlisted personnel in both the active and reserve components. In addition to generating cost savings, the proposed reforms sustain the current force size and shape.